TOPOGRAPHY OF NUTRIENT FORAMINA OF ADULT DRY RADII IN SOUTH INDIAN POPULATION WITH A NOTE ON ITS SURGICAL RELEVANCE - JAKKA, LAKSHMI DURGA; CHANDIPRIYA, DASARI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of this study was to study the average length of adult dry radii in south Indian population, distribution of nutrient foramina, and foraminal index. Methods: This study was conducted using 200 dry, adult radii, obtained from the department of Anatomy at our institute. Fully formed radii of both sides and genders were included in the study. Length of each bone, distribution, and direction of nutrient foramina on diaphysis were studied with the help of a Vernier caliper. Later, foramen index was estimated for all bones using Hughes formula. The data were tabulated and analyzed statistically. Results: Average length of radii in the study was 23.37±1.65 cm. All radii had their nutrient foramina, directed proximally. About 2% of the study sample had double nutrient foramina. Increased number of foramina had no effect on length of bone. As many as, 57.5% of radii had nutrient foramen on the anterior surface of shaft. Mean foramen index was 34.24±4.75. Conclusion: This study provides population-specific data regarding length of adult radii and topography of nutrient foramina of adult radii. An attempt was made to acknowledge its relevance while harvesting a vascular graft.